On the Drivers of Clean Production: Firms' Global Value Chain Positioning - Finn Ole Semrau (ZBW - Leibniz Information Centre for Economics, 2022)
Industries that occupy upstream positions in global value chains (GVCs) - being positioned closer to the raw product - produce proportionately more CO2-intensive. However, firms are heterogeneous, even in narrowly defined industries. In this paper, I empirically investigate whether the relationship between upstreamness and CO2 emissions, measured in absolute and relative terms, holds within industries at the firm level. Using granular data of Indian manufacturing firms and controlling for established drivers of clean production, I reveal that firms producing products closer to final consumption produce less CO2-intensive. I corroborate the finding by using a 2-SLS instrumental variable approach. Interestingly, I find that exposure to importing countries with stringent environmental policies attenuates the link between upstreamness and dirty production. The latter finding suggests the imperative of technology upgrading for dirty upstream producers aiming to remain competitive in international markets.
Keywords: F14; F18; O13; Q56; 330; Environment and trade; environment and development; CO2 intensity; global value chains; sustainable development